Genetic Diversity and Virulence Profiling of Multi-Drug Resistant Escherichia coli of Human, Animal, and Environmental Origins - Asfand Yar; Muhammad Adil Choudary; Abdul Rehman; Abid Hussain; Amina Elahi; Farooq ur Rehman; Ahmed Bilal Waqar; Abdulrahman Alshammari; Metab Alharbi; Muhammad Atif Nisar; Mohsin Khurshid; Zaman Khan (MDPI AG, 2022)
Rapid urbanization has increased human-animal interaction and consequently enhanced the chances to acquire zoonotic diseases. The current investigation is focused to uncover the genetic diversity of multidrug-resistant E. coli strains between different ecologies (i.e., humans, livestock, and environment) at the molecular level by employing antimicrobial resistance profiling, virulence genes profiling, and microbial typing approach using ERIC PCR. Based on multiple antibiotic resistance, overall, 19 antibiotic resistance patterns (R1-R19) were observed. Most of the strains (49/60) were detected to have the combinations of stx, eaeA, and hlyA genes and considered STEC/EPEC/EHEC. A total of 18 unique genetic profiles were identified based on ERIC-PCR fingerprints and most of the strains (13) belong to P1 whereas the least number of strains were showing profiles P7 and P8-P11 (one member each profile). The calculated values for Shannon index (H) for human, animal, and environment are 1.70, 1.82, and 1.78, respectively revealing the highest genetic diversity among the E. coli strains of animal origin. The study revealed that drug-resistant pathogenic E. coli strains could be transmitted bidirectionally among the environment, humans, and animals.